A fluorometric assay to determine the protective effect of glucose-6-phosphate dehydrogenase (G6PD) against a Plasmodium spp. infection in females heterozygous for the G6PD gene: proof of concept in Plasmodium falciparum - Rumaseb A. (2023)
Objective: Glucose-6-phosphate dehydrogenase (G6PD) deficiency offers some protection against malaria; however, the degree of protection is poorly described and likely to vary with G6PD genotype and Plasmodium species. We present a novel approach to quantify the differential invasion rates of P. falciparum between G6PD deficient and normal red blood cells (RBCs) in an ex vivo model. A flow-cytometry based assay was developed to distinguish G6PD deficient and normal, parasitized and non-parasitized RBCs within the same sample. Venous blood collected from a G6PD heterozygous female was infected and cultured ex vivo with a laboratory strain of P. falciparum (FC27). Results: Aliquots of infected blood were assayed at schizont and subsequent synchronized ring stages. At schizont stage, 84.9% of RBCs were G6PD deficient of which 0.4% were parasitized compared to 2.0% of normal RBCs. In the subsequent ring stage, 90.4% of RBCs were deficient and 0.2% of deficient and 0.9% of normal cells respectively were parasitized. The pooled Odds Ratio for a deficient RBC to be parasitized was 0.2 (95% confidence interval: 0.18–0.22, p < 0.001) compared to a normal cell. Further studies are warranted to explore preferential parasitization with different G6PD variants and Plasmodium species.